Translation and silencing in RNA granules: a tale of sand grains - Pimentel, Jerónimo; Boccaccio, Graciela L. (Frontiers in Molecular Neuroscience, 2014)
The transcriptome at the synapse consists of thousands of messengers encoding a plethora of cellular functions, including an important number of receptors and ion channels and associated proteins. The concerted translational regulation of all these molecules contributes to the dynamic control of the synaptic strength. Cumulative evidence supports a role for dendritic RNA granules and mRNA-silencing foci in translational regulation, and several important RBPs ‒FMRP, FUS/TLS, TDP-43, Staufen, Smaug, Pumilio, CPEB, HuD, ZBP1 and DDX6 among others‒ form granules that contain dormant mRNAs repressed by multiple pathways. Recent reports indicate that RNA granules may contain stalled polysomes, and furthermore, active translation may occur in association with dendritic granules. Here we discuss the molecules and pathways involved in this continuum of RNA granules that contain masked mRNAs, mRNAs trapped in inactive polysomes or mRNAs engaged in translation.